Modified Target Diagram to check compliance of low-cost sensors with the Data Quality Objectives of the European air quality directive. (15th March 2022) - Yatkin, Sinan; Gerboles, Michel; Borowiak, Annette; Davila, Silvije; Spinelle, Laurent; Bartonova, Alena; Dauge, Frank; Schneider, Philipp; Van Poppel, Martine; Peters, Jan; Matheeussen, Christina; Signorini, Marco
Abstract: The modified Target Diagram (MTD) was developed to evaluate the performance of low-cost sensors (LCS) for air quality monitoring in comparison with reference methods by reporting relative expanded uncertainty and its contributors. An MTD provides several pieces of information, including compliance with regulation, sources of error and how to diminish them, completeness and validity of LCS calibration etc. It allows the user to examine the effect of selecting different regression types and residual fitting on the LCS measurement uncertainty. The ordinary least squared regression with fitted residuals and dynamic between reference analyser uncertainty rather than constant ones yielded more realistic LCS measurement uncertainty compared to other options. The MTD is a fast visual tool to extract several pieces of information on evaluation of any candidate method against reference method. Highlights: A graphical tool to evaluate performances of sensors was developed. Uncertainty of sensors and its' contributors can be displayed. Checking compliance of sensors with legislation is easy and fast. Several other information can be extracted.